ACADEMIC WRITING SKILLS DEMONSTRATED IN UNIVERSITY STUDENTS’ FINAL YEAR PROJECT REPORTS, AND IMPLICATIONS ON THE TEACHING OF ENGLISH FOR ACADEMIC PURPOSES, IN THE ARAB WORLD - Al Husseini, Suleiman Salem (European Scientific Journal, ESJ, 2014)
This study highlights the academic writing skills that English as a Foreign Language (EFL) Arab students demonstrate in their final year project reports, and identifies the report’s constituent features such as topics, rhetorical forms, layout and structures. The study also elaborates on how the design of English for Academic Purposes (EAP) courses targeting students with similar background may be informed by such findings. The methodology of the study is underpinned by needs analysis, a genre approach to teaching EAP, and syllabus design. At the University of Nizwa, in the Sultanate of Oman, students coming from an Arabic background learn EFL to be able to meet the requirements and challenges of studying through the medium of English. Based on the finding that the final year reports have similarities and differences in terms of conventions and rhetoric, the author argues that a wide-angle approach might be more appropriate to teaching the language skills that the students need for writing a final year project report.